Spatial patterns of single nucleotide polymorphisms (SNPs) support a scenario of secondary contact in Iberian honey bees (Apis mellifera iberiensis) - Pinto, M. Alice (2018)
Dissecting diversity patterns of organisms endemic to Iberia has been truly challenging for a variety of plant and animal taxa, and the Iberian honey bee (A. m. iberiensis) is no exception. Here we used a genome-wide data set of 309 neutrally-tested SNPs, scattered across the 16 honey bee chromosomes, which were genotyped in 711 honey bee individuals. These SNPs were analyzed along with an intergenic locus of the mtDNA. The two markers revealed the existence of a strong and concordant structure supporting a process of secondary contact.